Refractive results after cataract surgery using Optical biometry - Hussain, Mehvash; Quraishy, Muhammad Muneer; Akram, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the refractive outcome of optical biometry (Nidek AL-scan) after elective phacoemulsification in a study of 30 eyes. Study Design: Descriptive case series. Place and Duration of Study: Elective cataract surgeries done at a private clinic from July 2015 to June 2016 were selected and their records were analyzed. Material Methods: The measurements of IOL calculation was done using optical biometry with partial coherence interferometry (Nidek AL-scan) that provides information about axial length, central keratometry, white to white diameter and anterior chamber anatomical depth. SRK-T formula was used to calculate IOL power. All patients underwent a complete ophthalmological examination. Phacoemulsification with clear corneal incision of 2.75 mm was done and IOL was implanted in the bag (Alcon Acrysof SN60WF IOL and MA60AC IOL). Post-operative refraction was taken with autorefractor (Huvitz HRK-7000) after 4 weeks and it was compared with pre-operative objective refraction. Comparison of K readings taken by AL-scan and autorefractor were done. Results: We studied 30 eyes of 23 patients who underwent elective cataract surgery with foldable IOL. Post-operative spherical equivalent was plano in 53% of cases with mean of -0.05 after 4 weeks postoperatively. The mean keratometric power using autorefractor was 44.4 D while with AL-scan it was 44.7 D. There were no intraoperative complications or postoperative subjective complaints (such as halo or glare) in our patients. Conclusion: Intraocular lens power calculations done by optical biometry are easy to use, reliable and result in excellent refractive outcomes. Ultrasound biometry may still be required in case of mature and dense posterior subcapsular cataract.